Gestão do conhecimento organizacional na condução de projetos corporativos em tecnologia da informação-um caso prático - Roberto Luis Capuruco Gattoni (2000)
The improvement of the organizations competitiveness has brought a significant reduction ofthe products and services life cycle. Besides that, it has been noted a great increase in the number of new technological alternatives that can be used on the conception and development of new organizational solutions. Ihese new solutions can leverage the share of those organizations on the global markets. The real implementation of organizational knowledge management techniques and tools on project management can be an important competitive differential to the organizations from the ktiowledge era. This work presents an analysis of a real case study on the information technology area. This case shows that the use of knowledge management elements on the development ofenterprise projects arise as an important set of tools to the technological innovation.